Answer to Question #19870 in Geometry for jenny
positive odd integers.
(i)=(1+n)*n/2 we have p=sum( i=1 to n) (2a+2i-1)=(2a-1)*n+sum( i=1 to n)
(2i)=(2a-1)*n+2*sum( i=1 to n) (i)=(2a-1)*n+2*(1+n)*n/2=
and we see that n must divide p and it means that forn>1 we have that p not prime but it is contradiction so p cant be expressed
as the sum of two or more consecutive positive odd numbers
Need a fast expert's response?Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!